Isolation, Identification and Characterization of Yersinia Spp from Meat and Meat Products - Mohd Dzomir, Ahmad Zainuri (2005)
Three hundred and twenty two samples comprising of beef (94), chicken parts (1 14), pork (1 I), beef burger (47), chicken burger (30), chicken nugget (I), chicken frankfurter (lo), chicken carcass (20) and pork frankfurter (5) were examined for the presence of Yersinia. Samples were enriched in phosphate-buffered-saline at 25OC for 48h. Enriched samples were treated with 0.5% +potassium hydroxide (KOH) solution and then streaked onto Cefsulodin-lrgasan-Novobiocin (CIN) agar plates. 1/94 ( 1 I %) 16/47 (34.0%), 6/14 (5.3%), 1/30 (3.3%) and 1/20 (5.0%) of beef, beef burgers, chicken parts, chicken burgers and chicken carcass samples were contamhated with Yersinia spp. respectively. Yersinia spp. were not isolated from pork, chicken nugget and chicken frankfurter samples. Fifty-three isolates of Yersinia spp. were isolated from 25 (7.7%) positive samples and identified as Y. enterocolitica (29), Y. frederiksenii (18), Y. kristensenii (3) and Y, intennedia (3). Highest numbers of positive samples were obtained from Selangor (86.2%), followed by Negeri Sembilan (6.9%). 3.4% of the positive samples were obtained from Kuala Lumpur and overseas. In this study, Y. enterocolitica was defined as non sensu strict0 on the basis of biochemical properties not strictly fitting according to the scheme used for classification at the genus level. They were biochemically atypical, including Simmon's citrate-positive and Voges-Proskauer-negative. All Y. enterocolitica isolates were grouped into biotype 1A based on reaction to Dxylose, nitrate reduction and pyrazinamidase. The four related species: Y. frederiksenii, Y. intennedia and Y. kristensenii were readily distinguishable by sucrose, melibiose, rhamnose and raffinose fermentation. The result of serotyping of twenty Y. enterocolitica showed that eleven of them belonged to serotype 0:52,53; one isolate belong to serotype 0:41,42 and nine were untypable, delineating the isolates from pathogenic serotypes. In addition, Polymerase Chain Reaction (PCR) analysis indicated that Y. enferocolitica examined did not possessed any of the virulence marker genes that are characteristics of pathogenic strains. Antibiotic susceptibility analysis showed there was no difference in the susceptibilities of the four Yersinia species towards ampicillin, penicilin, cephalotin, bacitracin and chloramphanicol. All isolates (100%) were resistant to ampicilin, penicilin and cephalotin but all (1 00%) were sensitive to chloramphenicol. 1.96, 3.92, 5.88, 9.80 and 29.41 % of Yersinia isolates were resistant to gentamicin, nalidixic acid, streptomycin, tetracycline and cefaporazone, respectively. 98.04% of the isolates which were resistant to carbenicillin demonstrated weak activity of carbenicilin against the Yersinia. Multiple Antibiotic Resistance (MAR) index ranged from 0.36 to 0.64. Three plasmid patterns were observed among the Yersinia isolated. 31 (60.78%) of the isolates carried single plasmid and 20 (39.22%) of the isolates did not carry any plasmid. 21 (41 .la%), 8 (15.69%) and 2 (3.92%) of the isolates were harbor 54, 32 and 2.7 MDal plasmid size, respectively. The dendrogram obtained by comparative analysis of the pulsed field electrophoresis patterns clustered biotype 1A into three clusters (A, B and C). The PFGE result indicated that they (biotype 1A) were different from the pathogenic strains (control strains).